Health inequalities in Latin American and the Caribbean: Child, adolescent, reproductive, metabolic syndrome and mental health - Antonella Bancalari; Samuel G. Berlinski; Giancarlo Buitrago; María Fernanda García; Dolores de la Mata; Marcos Vera-Hernández (Inter-American Development Bank (IDB), 2023)
Health constitutes a fundamental aspect of our well-being. It is also a key factor in determining our contribution to market and non-market output. Health inequality refers to the unequal realization of health outcomes between different groups in the population. Systematic disparities in health outcomes and in access to health resources not only undermine basic principles of fairness and social justice but also contributes towards perpetuating poverty and disadvantage. In this chapter, we start by presenting evidence on how the burden of disease in Latin America and the Caribbean (LAC) has changed during the last 30 years. Consistent with the fall in fertility and population aging, the region has shifted from a burden of disease dominated by maternal, neonatal, and communicable disease in the 1990s to one dominated by cardiovascular disease, cancers, diabetes, and increasingly by mental health disorders. The poorest in the region are burdened by worst access to maternal care and higher levels of infant mortality and stunting. Despite being knowledgeable about contraceptive methods, young women in Latin America and the Caribbean have very high levels of teenage pregnancy with a steep socio-economic gradient. Noncommunicable diseases also affect the poor disproportionately in many countries. Finally, mental health is a growing source of lost days of healthy living among women and the poor. Overall, our results highlight that despite the epidemiological transition which is underway, socio-economic health disparities in the LAC region are still more important on early childhood and teenagerhood than in adulthood, at least as it pertains to the outcomes analyzed in this chapter. At the same time, we show that while socio-economic inequalities in child health are smaller in the richest countries, the contrary happens with inequalities in some adult outcomes.
Keywords: I14; I15; I12; D6; 330; contribution; Health inequality; women in Latin America; Mental health; socio-economic health disparities